Statistical upscaling of stochastic forcing in multiscale, multiphysics modeling - Vollmer, Charles T., author; Estep, Don, advisor; Tavener, Simon, committee member; Breidt, Jay, committee member; Cooley, Dan, committee member (Colorado State University. Libraries, 2019)
Modeling nuclear radiation damage necessarily involves multiple scales in both time and space, where molecular-level models have drastically different assumptions and phenomena than continuumlevel models. In this thesis, we propose a novel approach to explicitly coupling these multiple scales of the microstructure damage of radiation in materials. Our proposed stochastic process is a statistical upscaling from physical first principals that explicitly couples the micro, meso, and macro scales of materials under irradiation.
Keywords: materials modeling; multiscale; stochastic processes; multiphysics; cellular automata; probabilistic cellular automata